Orality, Inclusion and Equality in the EFL Primary Classroom - Licia Masoni (University of Bologna, 2021)
This paper describes the interplay between orality and inclusive English as a Foreign Language Teaching (in the primary classroom), with reference to the Italian context. Inclusive teaching is here understood as a teacher's ability to provide environments ensuring every pupil equal access to the English language. In the first part of the paper, a case is made for the need to implement the use of aural and oral communication in the EFL classroom, both in terms of letting children listen to the sounds of the new language (thus fostering comprehension skills) and enabling them to copy the teacher's sounds and words, or even express what they might already know. The second part of the paper focusses on the learner, and in particular on immigrant children who are trying to master the local language (Italian), native children who might have different levels of access to the foreign language outside school, depending on their socio-economic status, and children with specific learning difficulty. Finally, the paper briefly discusses the implications, both for in-service teachers and for university student teachers, of the implementation (and increase) of classroom orality.